2020
DOI: 10.1017/thg.2020.58
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profile and Body Composition in Twins Concordant and Discordant for Physical Exercise

Abstract: The aim of this study was to evaluate the differences in the metabolic profile and body composition of monozygotic (MZ) twins concordant and discordant for the practice of physical exercise. The sample consisted of 92 MZ twins (72.5% female and 27.5% male, mean age 25.4 ± 5.69 years), registered with the Brazilian Registry of Twins, residing in Natal, Brazil. Data collection was carried out between the years 2016 and 2018. On day 1, subjects underwent a whole-body fitness evaluation, including measures of weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…It refers to the physical activities with certain intensity, frequency, and time that individuals carry out in their spare time for the main purpose of health ( Song, 2001 ). Many studies have shown that physical exercise has a positive protective effect on the level of individual cardiopulmonary level, muscle tissue, and brain cognition, and has a good therapeutic effect on metabolic diseases ( Sarmento et al, 2017 ; Leal et al, 2018 ; Hernandez et al, 2019 ; Borges et al, 2020 ). So does physical exercise affect life satisfaction?…”
Section: Introductionmentioning
confidence: 99%
“…It refers to the physical activities with certain intensity, frequency, and time that individuals carry out in their spare time for the main purpose of health ( Song, 2001 ). Many studies have shown that physical exercise has a positive protective effect on the level of individual cardiopulmonary level, muscle tissue, and brain cognition, and has a good therapeutic effect on metabolic diseases ( Sarmento et al, 2017 ; Leal et al, 2018 ; Hernandez et al, 2019 ; Borges et al, 2020 ). So does physical exercise affect life satisfaction?…”
Section: Introductionmentioning
confidence: 99%